Design Features of Language - Coleman, J (Elsevier, 2006)
The design features of language are a set of characteristics, some of which are found in the communication systems of nonhuman animals, and some of which are thought to be unique to human language. By enumerating such properties, linguists have attempted to reveal some of the natural foundations of the human language faculty and to identify ways in which language is special and distinct from other communication systems. The list of features is reappraised in the light of recent research into the communicative abilities of nonhuman animals. © 2006 Elsevier Ltd. All rights reserved.